DEFORMATION-MECHANISM-BASED MODELING OF CREEP BEHAVIOR OF P91 STEEL - LI Bo; LIU XinBao; ZHU Lin; QUAN Chen; WANG Ni (Jixie qiangdu)
Creep behavior of P91 steel was studied by using a constitutive model based on deformation mechanism. Combined with the experimental data, it was found that the minimum creep rate has an obvious exponential relationship with the applied stress during creep, which was closely related to different deformation mechanisms. By introducing dislocation slip, dislocation climb and grain boundary slip into the traditional Norton power law equation, the creep behavior of P91 steel under the conditions of 580℃～620℃ and 135 MPa～200 MPa stress was simulated and analyzed. The results show that the creep curve of P91 steel can be well described by using this model, including the initial stage, steady stage and acceleration stage of creep. In addition, the results of model calculation and SEM analysis further show that the creep fracture form of P91 steel is transgranular fracture within the current temperature stress range.